ANTI-HELICOBACTER PYLORI ACTIVITY OF SUBSTITUTED BENZOTHIAZOLES: IN VITRO STUDY - REKHA.S; CHANDRASHEKHARA.S (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: Helicobacter pylori, originally classified as Campylobacter pylori, is a Gram negative, micro aerophilic, spiral-shaped, motile bacterium associated with gastritis, peptic ulcer, duodenal ulcer and chronic gastritis. Helicobacter pylori have been a major cause of peptic ulcer, gastric ulcer, duodenal ulcer disease and are an early risk factor for gastric carcinoma. This study has been undertaken for isolation of Helicobacter pylori form clinical specimens using culture technique and detection the role of this technique in the investigation of H. pylori infection. New series substituted benzothiazoles have been synthesized. Substituted benzothiazole has an antibacterial activity against a wide range of bacteria. However, in the present work its activity against Helicobacter pylori has been reported. Methods: The structures of the synthesized compounds were confirmed by FTIR, 1H NMR,13C NMR and Mass spectral analysis. The antimicrobial potential of substituted benzothiazoles was evaluated by agar plate disc diffusion method. Results: The newly synthesized compounds 6(a-d) were tested for their in vitro antibacterial activity against H. pylori by using the agar disc diffusion method. All of the synthesized compounds showed good antibacterial activity. However the antibacterial activity of the synthesized compounds against the tested organisms was found to be less than that of respective standard drug at tested dose level. Conclusion: Many of the compounds from the series have emerged as potent antibacterial agents endowed with moderate to good activity. The antimicrobial activity of the synthesized compounds against the tested organisms was found to be less than that of respective standard drug at tested dose level. In future study the activity of the compounds may be manipulated Â Keywords: Benzothiazole, Helicobacter pylori, duodenal ulcer, Gastric carcinoma,